Eksistensi Bangunan dan Kawasan Bersejarah di Kota Manado dan Peranannya sebagai Urban Heritage - Wuisang, Cynthia E.V; Siregar, Frits O.P; Mastuti, Faizah (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2018)
The development of Manado City reflects modern life in urban areas, particularly population growth, massive development and the dynamics of various activities. These qualities bring changes in the use of space in urban environmental functions and changes in city characteristics and developments. Hence deterioration in the quality and image of the city is usually unavoidable. Therefore it is necessary to anticipate change and plan the protection of environmental assets that are recognized as urban heritage. Manado City has a rich catalogue of buildings and historic areas that need to be understood and acknowledged as such. In the context of historic areas of a city the conservation and preservation of buildings and spaces is universally recognized, and this paper evaluates such historic sites in Manado. Research variables include buildings and spaces which reflect cultural and historic value. Qualitative methodology is applied, using photography (visual recording and documentation); in-depth interviews and the recorded perceptions of local people in Manado City. Results demonstrate that few buildings and historical sites which have been identified in this research have been protected. Several important historic buildings go unrecognized by local government, and consequently there is a lack of action in preserving the city’s urban artefacts and historic sites. Keywords: heritage building, historical sites, urban heritage, preservation, conservation, Manado